Long-term follow-up and patient satisfaction after reduction mammoplasty: Superomedial versus inferior pedicle - Mohamed Makboul; Mahmoud S. Abdelhamid; Ghada S. Al-Attar (Indian Journal of Plastic Surgery)
Background: Surgery for hypertrophied breasts represents a challenge for plastic surgeons. The search for a good post-surgical cosmetic breast has led to the development of many techniques. Objectives for reduction mammoplasty are to achieve elevated, symmetrical breasts, a round shape, good projection, small cicatrices that are not very perceptible, and a lasting result. Patients and Methods: This study was carried out on sixty cases who had done reduction mammoplasty from January 2009 to December 2014. All patients were examined and were asked for late post-operative results and overall patients’ satisfaction. Results: Long-term projection and contour of the breast were more satisfactory among patients who had superomedial pedicle with a statistically significant difference. No statistically significant difference was observed between patients underwent either superomedial or inferior pedicle reduction mammoplasty with regard to breast shape symmetry, nipple symmetry and sensation. The mean score for satisfaction was higher among patients who underwent superomedial pedicle rather than the inferior pedicle method. Conclusion: The superomedial pedicle shows better long-term cosmetic results.